A Novel Peptide Derived from Ginger Induces Apoptosis through the Modulation of p53, BAX, and BCL2 Expression in Leukemic Cell Lines - Chatupheeraphat, Chawalit; Roytrakul, Sittiruk; Phaonakrop, Narumon; Deesrisak, Kamolchanok; Krobthong, Sucheewin; Anurathapan, Usanarat; Tanyong, Dalina (Planta Medica, 2021)
Despite the efficacy of chemotherapy, the adverse effects of chemotherapeutic drugs are considered a limitation of leukemia treatment. Therefore, a chemotherapy drug with minimal side effects is currently needed. One interesting molecule for this purpose is a bioactive peptide isolated from plants since it has less toxicity to normal cells. In this study, we extracted protein from the Zingiber officinale rhizome and performed purification to acquire the peptide fraction with the highest cytotoxicity using ultrafiltration, reverse-phase chromatography, and off-gel fractionation to get the peptide fraction that contained the highest cytotoxicity. Finally, a novel antileukemic peptide, P2 (sequence: RALGWSCL), was identified from the highest cytotoxicity fraction. The P2 peptide reduced the cell viability of NB4, MOLT4, and Raji cell lines without an effect on the normal peripheral blood mononuclear cells. The combination of P2 and daunorubicin significantly decreased leukemic cell viability when compared to treatment with either P2 or daunorubicin alone. In addition, leukemic cells treated with P2 demonstrated increased apoptosis and upregulation of caspase 3, 8, and 9 gene expression. Moreover, we also examined the effects of P2 on p53, which is the key regulator of apoptosis. Our results showed that treatment of leukemic cells with P2 led to the upregulation of p53 and Bcl-2-associated X protein, and the downregulation of B-cell lymphoma 2, indicating that p53 is involved in apoptosis induction by P2. The results of this study are anticipated to be useful for the development of P2 as an alternative drug for the treatment of leukemia.
Keywords: ginger; antileukemic peptide; leukemia; apoptosis; p53